2018
DOI: 10.1016/j.jpainsymman.2018.08.010
|View full text |Cite
|
Sign up to set email alerts
|

Caregivers' Experiences With Medical Aid-In-Dying in Vermont: A Qualitative Study

Abstract: Although AID is often presented as a simple matter of individual choice and autonomy, most patients who pursue it do so with tremendous support from caregivers, who are in turn deeply implicated, socially and morally, in the process. Including caregivers in education and planning, where warranted, can mitigate feelings of unpreparedness and ensure a smoother experience for everyone involved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(43 citation statements)
references
References 33 publications
0
42
0
1
Order By: Relevance
“…Nineteen articles, representing fourteen studies, met our inclusion criteria and were included in the review (4,7,(9)(10)(11)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31). Ten studies (eleven articles) used a qualitative design (4, 7, 9-11, 18, 23, 24, 26-28).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Nineteen articles, representing fourteen studies, met our inclusion criteria and were included in the review (4,7,(9)(10)(11)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31). Ten studies (eleven articles) used a qualitative design (4, 7, 9-11, 18, 23, 24, 26-28).…”
Section: Resultsmentioning
confidence: 99%
“…The patients' death appeared to be anticipated, and it appeared that the circumstances of the death such as the rituals and place of death were decided with considerable attention and care. Families appeared to navigate between the awareness of the limited time left with the patients and the organisation of the farewell which sometimes disturbed them (7,9,24) . Some families valued the possibility of being aware of the farewell date well in advance, whereas Dees et al reported that Dutch families might be unfamiliar with the emotional task of organising the final farewell for someone who has limited time left to live (7).…”
Section: (4) Experiencing the Final Farewellmentioning
confidence: 99%
See 1 more Smart Citation
“…Professional help is unavailable or inadequate; the illness causes family tension; caregiving demands are unrelenting; the death is unexpected, and the caregiver feels unprepared [27, 34, 35, 42, 47-51, 53, 55, 56, 60] Healthcare providers are unwilling to discuss hastened death; the patient cannot achieve hastened death and suffers; in Switzerland, the caregiver experiences ongoing distress about breaking social norms to assist in hastened death [15,57,70] No resolution Caregiver lives in state of constant vigilance; caregiver cannot process or mourn the patient's death [32,40,51,60,61] [45,46,49,[55][56][57][58] Events that align with patient's wishes [15,17] Distress Patient decline, conflict between exhaustion and increasing patient needs, social isolation, breaking a promise to the patient, family conflict [27, 29, 30, 36, 37, 42, 45-51, 53, 56, 57, 60, 61, 63] Complicated dying, moral distress about patient choice to die [15,[17][18][19][20][67][68][69][70][71] "The 'I-killed-my-mom thing' is big, still. Because it's the truth-how do I come to some resolution around that?"…”
Section: Unfavourable Resolutionmentioning
confidence: 99%
“…To date, one systematic review evaluated the experience of caregivers specifically in the context of aid in dying (including assisted suicide and euthanasia) [14]. Studies of caregiving during assisted dying describe caregiving roles such as helping the patient navigate the medical and legal hurdles to obtaining a lethal prescription, assisting with preparation of the medication, bearing witness to the death, and orchestrating the completion of patients' wishes before, during, and after death [15][16][17][18][19][20]. Comparing the experiences of caregivers in aid in dying with those in other end of life trajectories can inform practice for clinicians supporting patients and caregivers before, during, and after hastened death.…”
Section: Introductionmentioning
confidence: 99%